Bioversity International Annual Report 2014 - Bioversity International (Bioversity International, 2015)
The Bioversity International Annual Report 2014 contains highlights of Bioversity International research activities to deliver scientific evidence, management practices and policy options to use and safeguard agricultural and tree biodiversity to attain sustainable global food and nutrition security. The report also includes information about our research and funding partners, and our Board of Trustees.